2021
DOI: 10.3389/fped.2021.765306
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Associated Hyperkalemic Cardiac Arrest in Neonatal, Infant, and Pediatric Patients

Abstract: Red blood cell (RBC) transfusions are a life-saving intervention, with nearly 14 million RBC units transfused in the United States each year. However, the safety and efficacy of this procedure can be influenced by variations in the collection, processing, and administration of RBCs. Procedures or manipulations that increase potassium (K+) levels in stored blood products can also predispose patients to hyperkalemia and transfusion-associated hyperkalemic cardiac arrest (TAHCA). In this mini review, we aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 103 publications
0
16
0
Order By: Relevance
“…25,26 The effect of blood—irradiated or not—on potassium blood concentration is directly related to the rate of infusion and blood age. 19,27…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The effect of blood—irradiated or not—on potassium blood concentration is directly related to the rate of infusion and blood age. 19,27…”
Section: Discussionmentioning
confidence: 99%
“…Age groups were defined as follows; Group 1: ≤28 days old (neonate), Group 2: 29 days to <1 year old, Group 3: 1-5 years old, Group 4: 6-10 years old, and Group 5: 11-<18 years old. Since many case reports in the literature were reported on neonates, 2,3 ≤28 days old group was analyzed separately in this study. Therefore, 12 patients in each age group, a total of 60 patients were investigated as a control group (non-TAH group).…”
Section: Data Collectionmentioning
confidence: 99%
“…Hyperkalaemia represents a key component of the pRBC storage lesion in which biochemical, metabolic and structural alterations occur within pRBCs in a time-dependent fashion, with a 3.76-fold increase in potassium concentration observed after three weeks [17 ▪ ]. An in-vitro study demonstrated a direct link between supernatant from pRBCs stored for longer periods, hyperkalaemia and adverse electrocardiogram changes [18].…”
Section: Mechanisms Of Biochemical Disturbancementioning
confidence: 99%
“…With their smaller circulating volumes, paediatric patients are at particular risk of transfusion-related hyperkalemic cardiac arrest (TRHCA) [17 ▪ ], with increased age of pRBCs and concomitant acidosis or hypocalcaemia compounding the risk [52]. A single unit of pRBCs has been shown to raise [K] by 0.09 mmol/l among critically ill adults [53 ▪ ].…”
Section: Hyperkalaemiamentioning
confidence: 99%